Efforts to Increase Student Awareness in Islamic Education Learning through Quantum Learning Model at SMA Negeri 1 Indrajaya - Yusrida; Agustina, Ritazar; Yani, Ahkam (Jurnal Profesi Guru Indonesia, 2024)
This study aims to enhance student learning outcomes in Islamic Education at SD Negeri 1308 Hasahatan Julu through the implementation of the Quantum Learning model. Using a Classroom Action Research (CAR) approach, the research involved 30 fifth-grade students and focused on improving their participation, comprehension, and academic performance. The findings revealed a significant improvement in students' engagement, understanding, and retention of Islamic Education content following the use of the Quantum Learning model. The interactive and student-centered activities encouraged critical thinking, collaboration, and real-life application of Islamic principles, leading to more meaningful learning experiences. In conclusion, the Quantum Learning model proved to be an effective approach for enhancing student achievement and fostering a deeper connection to the subject matter.